New housing supply in Australia – a 10 year analysis - Rowley, Steven (2020)
Almost 1.5 million new homes were built in Australian in the 10 years from 2006 to 2016 but the growth of housing stock in each state and territory was uneven, ranging from 26 per cent in Western Australia to just 12 per cent in New South Wales. Over this period, housing supply varied in mainland capital cities – some delivering more housing in inner areas (Sydney, Melbourne) while others have seen housing concentrated in outer areas (Adelaide, Perth).